EVALUATION OF THE INTENSITY FREIGHT AND VEHICLES FLOWS - and and (Municipal economy of cities. Series: «Economy science», 2016)
The intensity of intercity freight and vehicles flows on a network of public national and international roads of Ukraine is researched. The basis of this study is an annual all-Ukrainian freight correspondence matrix. In calculating the daily intensity of intercity traffic flows is taken into account their unevenness during work and free days and also a structure of the transport flow which consist small and heavy-duty vehicles flows. The resulting values of daily volumes of goods and vehicles movement have shown that it is possible on this base to estimate not only daily cargo owner’s needs for intercity freight transportation, but also provide an estimate of the country freight traffic flows intensity. Keywords: intensity, traffic flow, intercity freight transportation, original-destination matrix.